Doctor, am I allowed to drive? A practical case-based guide on fitness to drive in cardiovascular diseases adapted from the Swiss model - Achim Alexandru (Sciendo, 2023)
From 2016 onwards, a group of cardiologists initially formed in 2013 took the initiative to regulate and standardize the rights of European citizens suffering from diverse cardiovascular conditions at the European level. Subsequently, the Romanian government embraced and incorporated these recommendations into law a year later. This process addressed several important new aspects, including stents, myocarditis, and various cardiomyopathies, with a focus on striking a balance between the individual's right to drive a vehicle and the need to safeguard the lives of others. The Romanian law, however, is vague and states that "candidates or drivers from the indicated groups can be issued or renewed their driving licenses only after the condition in question has been effectively treated and subject to the opinion issued by the specialist cardiology doctor and, depending on a case, by performing a periodic medical check" but does not clearly specify how and for how long and to whom exactly the driver's license should be suspended. Interestingly, Switzerland, despite not being an EU member, developed its own set of recommendations three years later, drawing strong inspiration from the German guidelines, which in turn personalized its indications (being the European country with the most publications in this field). A refinement of the refinement, one could say. The indications are clear, precise, and structured in a point-by-point fashion. The purpose of this review is to explore the Swiss guidelines on fitness to drive in cardiovascular diseases interactively, with discussions on fictitious cases, in the hope that doctors will be able to become more familiar with these rigid and often interpretable indications and implement them in their daily practice.